Open Peer Review by a Selected-Papers Network - Lee, Christopher (Frontiers in Computational Neuroscience, 2012)
A Selected-Papers (SP) Network is a network in which researchers who read, write and review articles subscribe to each other based on common interests. Instead of reviewing a manuscript in secret for the Editor of a journal, each reviewer simply publishes his review (typically of a paper he wishes to recommend) on the SP network, which automatically forwards it to his subscribers. I present a three phase plan for building a basic SP network, discovering and measuring the detailed structure of research communities, and transforming the SP network itself into an effective publisher of research articles in areas that are not well-supported by existing journals. I show how the SP network provides a new way of measuring impact, catalyzes the emergence of new subfields, and accelerates discovery in existing fields, by providing each reader a fine-grained filter for high-impact.